A proposed program for the department of pastoral services in Charitas Hospital at Palembang, Indonesia - Sihombing, Bernadette (Animo Repository, 1978)
This study proposes a program for a Department of Pastoral Services with counseling staff in Charitas Hospital in Palembang, extending its services not only to the patients but also to the personnel in the institution. A survey method was followed in the study with the use of questionnaires A for patients and questionnaire B for personnel. The subjects of the study were the patients and the personnel of Charitas Hospital Palembang. The desired sampling was 50 per cent of the admitted patients during the time of the administration of the questionnaire. However, this excluded the seriously ill patients and others who are not strong enough to answer the questionnaire. The selection of subjects was done by systematic random sampling. Out of the 140 patients who were fit to answer the questionnaire, 67 were chosen to be respondents. From among the personnel, 112 subjects were chosen, once again by systematic random sampling, with the aid of table of Random Numbers. Statistical treatment used was taking the percentages of the responses and ranking them according to the average weighted mean values. From the findings of the study, the following conclusions were formulated. 1) During the period of their confinement, the patient will be able to accept and integrate suffering into their lives, with as little emotional disturbance as possible, in a meaningful manner with the organization of a Pastoral Counseling. 2) The family, which is of importance to the immediate environment of the patient, will be expected to give him the support and encouragement he needs. 3) The personnel of the hospital will develop into men and women of service, who are aware of their dignity and uniqueness and manifest self-direction in their personal and professional lives. They should become responsible and caring persons, fully available to their patients. In order to meet these general objectives, the following services and activities have been suggested: 1) Liturgical and Prayer Service 2) Administration of the Sacraments